Correlation and Path Coefficient Analyses in Sugarcane - Chaudhary, Rewati R; Joshi, Bal K (Nepal Agriculture Research Journal, 2010)
This study was conducted to determine the contribution of different traits to cane yield in sugarcane (Saccharum officinarum L). Sixty-five clones were evaluated in a replicated field experiment at Sugarcane Research Programme, Jitpur, Nepal in 2003 for six morphological characters under irrigated conditions. Analysis of variance revealed significant differences for all the characters studied. Cane yield showed positively and highly significant correlation with single cane weight, stalk length and millable cane number. There was also positively significant correlation of cane diameter and number of internode with cane yield. Length of internode had positive non-significant correlation with cane yield. Single cane weight had the highest positive direct effect on cane yield followed by millable cane number. Stalk diameter and stalk length was positively and significantly correlated with cane yield, which was due to indirect effect of single cane weight. Results indicate that the genotypes should be selected on the basis of single cane weight and millable cane number for getting higher sugarcane yield. Key words: Cane yield; correlation; path coefficient; sugarcane DOI: 10.3126/narj.v6i0.3340 Nepal Agriculture Research Journal Vol.6 2005 pp24-27